2016
DOI: 10.7322/jhgd.119238
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the cycle of domestic violence against women

Abstract: Introduction: Violence against Women (VAW) has been produced under the hierarchical organization of male dominance in social relations between genders. It is a type of social relationship that is historically bounded, culturally legitimized and cultivated, in which the woman is exposed to objective and subjective aggression, both in public as well as private sectors. The consequences of the violence suffered by women materialize in biological, psychological and social harms that hamper them fully experiencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
17

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 19 publications
0
23
0
17
Order By: Relevance
“…Violence in the family environment accounts for a significant proportion of the morbidity and mortality rates in Brazil We found that adolescents and adults (10)(11)(12)(13)(14)(15)(16)(17)(18)(19) and 20-59 years old) are the age groups at risk for DV. Violence against adolescents and young adults is an important cause of early mortality and reduced life quality 25 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Violence in the family environment accounts for a significant proportion of the morbidity and mortality rates in Brazil We found that adolescents and adults (10)(11)(12)(13)(14)(15)(16)(17)(18)(19) and 20-59 years old) are the age groups at risk for DV. Violence against adolescents and young adults is an important cause of early mortality and reduced life quality 25 .…”
Section: Discussionmentioning
confidence: 93%
“…Given Brazil's size and socio-cultural diversity, there are also significant regional differences in the distribution of violence across the country 16 . However, few studies have analyzed the distribution and variation of DV throughout the country 17 . DV has a significant impact on morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…The unfavorable characteristics and living conditions of the pregnant women subjected to IPV can be seen from the perspective of gender analysis [36][37][38][39] . When deprived of the autonomy to fully exercise their social functions, such as access to education, paid jobs, health services and other public policies of social support, women in general submit themselves to a hierarchy of male power that is socially and culturally constituted in many societies, and in particular, in countries with low indicators of human and social development 1 .…”
Section: Fewer Than Nine Years Referencementioning
confidence: 99%
“…The fact that the victim is abused and continues to live near the offender causes mental health to be affected 24 . In this study, most of the victims presented emotional, psychological, and behavioral disorders due to sexual violence, which, fortunately, can be reduced by the mental health treatment offered by RESAVAS.…”
Section: Discussionmentioning
confidence: 99%
“…DOI: http://dx.doi.org/10.7322/jhgd.123611 J Hum Growth Dev. 2017; 27(2): 228-234 Sexual abuse characteristics in Santo André, São Paulo, Brazil: from victims to aggressors, from diagnosis to treatmentThe fact that the victim is abused and continues to live near the offender causes mental health to be affected 24 . In this study, most of the victims presented emotional, psychological, and behavioral disorders due to sexual violence, which, fortunately, can be reduced by the mental health treatment offered by RESAVAS.…”
mentioning
confidence: 99%